PENANGGULANGAN KEKERASAN YANG DILAKUKAN OLEH NARAPIDANA DI LEMBAGA PEMASYARAKATAN PEREMPUAN KELAS IIA JAKARTA - Cristoper; Zein Sgn, Subhan (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2025)
One of the cases of violence that occurs among prisoners is a problem that has not been resolved until now. The problems include the legal regulations regarding violence committed by female prisoners in the Class IIA Jakarta Penitentiary and the procedures for dealing with violence between female prisoners in the Class IIA Jakarta Penitentiary? The purpose of this study was to determine the handling of violence between female prisoners in the Class IIA Jakarta Penitentiary. This research method uses normative research, namely research conducted by analyzing written laws from library materials or secondary data. The results of this study concluded that the legal regulations regarding violence committed by female prisoners in the Class IIA Jakarta Penitentiary are regulated in Law Number 22 of 2022 concerning Corrections, Government Regulation Number 99 of 2012 concerning Amendments to Government Regulation No. 32 of 1999 concerning Requirements and Procedures for the Implementation of the Rights of Correctional Residents, Regulation of the Minister of Law and Human Rights of the Republic of Indonesia No. 33 of 2015 concerning Security in Prisons and Detention Centers, namely Security and Order Disturbances and SOP for Class II A Jakarta Prisons No. W.10.PAS.PAS.4-OT.02.02-2024 which contains the imposition of Disciplinary Punishments on Inmates. Handling violence between female prisoners in Class IIA Jakarta Women's Penitentiary Organizing educational programs that focus on awareness of violence, installing surveillance cameras in strategic areas and conducting routine patrols. The suggestion of this research is that the Government through regulations in the form of Government Regulations or Ministerial Regulations regulate strict sanctions for prisoners who violate or still commit acts of violence in prisons.